PENGARUH ALOKASI PAJAK ANTAR PERIODE, INVESTMENT OPPORTUNITY SET DAN LIKUIDITAS TERHADAP KUALITAS LABA - Yoga Anisa Nurhanifah; Tresno Eka Jaya (Fakultas Ekonomi, Universitas Negeri Jakarta, 2014)
This research aimed to examine the effect of interperiod tax allocation, investment opportunity set and liquidity on the quality of earnings in companies listed at Indonesia Stock Exchange (BEI) during 2010 – 2012.The data collected in this research include corporate financial statement data for 2009, 2010, 2011 and 2012. The number of samples collected was sixty-eight (68) manufacturing companies that have met the criteria the researchers used purposive sampling.Result from the model shows that in 5% significance indicates that the interperiod tax allocation is measured by using deffered tax expense and deffered tax income have no significant influence on earnings quality, investment opportunity set is measured by the proxy market value to book value asset and liquidity is measured by the proxy current ratio have negative significant influence on earnings quality.The coefficient of determination (R2) is 0,313 which indicates that the model can explain the influence of independent variables to dependent variable of 31,3%. Keywords: interperiod tax allocation, investment opportunity set, liquidity, earnings quality, earnings response coefficient (ERC)